Post-traumatic elbow stiffness: etiology, risk factors and current treatments - Fan, Maoqiang; Xu, Fan; Fei, Chen; Liu, Yao; Yang, Zhongtao; Song, Zhe (Frontiers in Surgery, 2025)
Post-traumatic elbow stiffness is a major cause of functional impairment after elbow trauma, affecting 10%–15% of patients. A 50% reduction in elbow range of motion can lead to an 80% decline in upper limb functionality, significantly impairing work performance and social participation. Based on a systematic search of Pub Med, Web of Science, China Knowledge Net and other databases, this paper systematically reviewed the diagnosis and treatment of post-traumatic elbow stiffness. While open and arthroscopic lysis remain effective when nonoperative treatment fails, the timing of surgery and the duration of postoperative immobilization remain controversial. Early and individualized rehabilitation is critical, and future research will focus on optimizing individualized treatment protocols and multidisciplinary treatment modalities.